Renewable energy and climate change - Quaschning, Volker 1969-; Jourdan, Hedy (New Delhi, India Wiley India, 2010)
This dazzling introductory textbook encompasses the full range of today's important renewable energy technologies. Solar thermal, photovoltaic, wind, hydro, biomass and geothermal energy receive balanced treatment with one exciting and informative chapter devoted to each. As well as a complete overview of these state-of-the-art technologies, the chapters provide: clear analysis on their development potentials; an evaluation of the economic aspects involved; concrete guidance for practical implementation; advice on how to reduce your own energy waste.
Our hunger for energy -- The climate before the collapse? -- From wasting energy to saving energy and reducing carbon dioxide -- Carbon-free energy - vision or utopia? -- Photovoltaics - energy from sand -- Solar thermal systems - year-round heating from the sun -- Solar power plants - even more energy from the sun -- Wind power systems - electricity from thin air -- Hydropower plants - wet energy -- Geothermal energy - power from the deep -- Heat pumps - from cold to hot -- Biomass - energy from nature -- The hydrogen industry and fuel cells -- Sunny prospects - examples of sustainable energy supply.
Authorized reprint of Wiley India, 2012.
Includes bibliographical references (p. 300-302) and index.
Keywords: Renewable energy sources; Climatic changes